2SPD-024 Shortages of medicines in hospital: results of a survey on the perception of health workers in the wards VSV real world. (24th March 2020) - Zovi, A; Musazzi, UM; Cilurzo, F; Minghetti, P
Abstract : Background and importance: Medicine shortages in Italy are an increasing phenomenon with significant impact on clinical activity. Aim and objectives: The aim of the study was to analyse the phenomenon, creating monitoring methods that can support the health workers (HW) involved in the problem. Material and methods: The hospital pharmacy (HP) developed a survey for HW, aimed at determining which types of drugs are most subject to unavailability, incidence and average duration of the phenomenon, approach used in managing any criticality and the impact on clinical practice. Results: A total of 59 HW from 14 different departments were interviewed. The classes of drugs reported most were: antibiotics (38.0%), corticosteroids (10.6%), gastroprotectors (8.8%), antihypertensives (7.1%), benzodiazepines and psychostimulants (5.2%), nutritional agents (4.4%), antihistamines (4.4%), blood products (3.5%), biologicals (2.6%) and others (14.8%). In 88% of the shortages, at least one medicine in the reference period (12 months) was reported, with an average duration of 2–8 weeks. Thirty-four per cent of respondents stated that the shortage of drugs had a negative impact—namely, the effect was perceived as very relevant in 5.9% of reporter cases since HW had to wait for the Italian Medicines Agency Nulla Osta for parallel importation; and relevant in 41.2% of cases, as HW had to wait for the HP to obtain supplies. In the remaining 52.9%, the impact was judged to be minor due to the presence of alternative therapeutic solutions. Specifically, in 11.4% of cases, a generic medicine was prescribed, based on the same active substance (AS) but with a different pharmaceutical form (8.6%) or different dosage (14.3%), and in the remaining 65.7% a medicine contained a different AS. The 17% of HW stated that the deficiency had never been solved, as in the case of oxacillin 1 g vials, ceftazidime 2 g vials, lysine acetylsalicylate 500 mg vials and danazol 200 mg tablets. Conclusion and relevance: The data collected confirm that the phenomenon of shortages is growing, highlighting the classes of medicines that are to be monitored to prevent the phenomenon. The tool used may be useful for improvement of the activity and efficiency of HP, with the aim of reducing the negative effects on daily clinical activity through constant comparisons between HW and HP. References and/or acknowledgements: No conflict of interest.